Identification of a DNA Damage Response and Repair-Related Gene-Pair Signature for Prognosis Stratification Analysis in Hepatocellular Carcinoma - Chen, Yi; Huang, Mengjia; Zhu, Junkai; Xu, Li; Cheng, Wenxuan; Lu, Xiaofan; Yan, Fangrong (Frontiers in Pharmacology, 2022)
Background: Nowadays, the cause of hepatocellular carcinoma (HCC) mortality and recurrence remain at a high level, the 5-year survival rate is still very low. The DNA damage response and repair pathway (DDR) may affect HCC patients' survival by influencing tumor development and therapeutic response. It is significant to identify a prognostic DDR-related gene signature to predict the outcome of patients. Methods: Level 3 mRNA expression and clinical information were extracted from the TCGA website. The GSE14520 datasets, ICGC-LIRI datasets, and a Chinese HCC cohort were served as validation sets. Univariate Cox regression analysis and LASSO-penalized Cox regression analysis were performed to construct the DDR-related gene pairs (DRGPs) signature. Kaplan-Meier survival curves and time-dependent receiver operating characteristic (ROC) analysis curves were calculated to determine the predictive ability of this prognostic model. Then, a prognostic nomogram was established to help clinical management. We investigated the difference in biological process between HRisk and LRisk by several enrichment analysis. TIDE algorithm and R package “pRRophetic” were applied to estimate the immunotherapeutic and chemotherapeutic response. Results: We constructed the prognostic signature based on 23 DDR-related gene pairs. The patients in the training datasets were divided into HRisk and LRisk groups at median cut-off. The HRisk group have significantly poor OS than LRisk group, and the signature was an independent prognostic indicator in HCC. Furthermore, a nomogram of the riskscore combined with TNM Stage was constructed and detected by calibration curve and decision curve. Lower riskscore associated with higher expression of HBV oncoproteins, metabolism pathways and patients in LRisk group might be more beneficial from immunotherapy; while HRisk presented upregulated DDR-relevant pathway and cell cycle process, and more frequently TP53 mutated, but CTNNB1 mutations in HCC were exclusive with TP53. For chemotherapeutic drugs commonly used in HCC, the HRisk group was highly sensitive to 5-Fluorouracil while LRisk group presented with a significantly higher response to Gefitinib and Gemcitabine. Conclusion: Overall, we developed a novel DDR-related gene pairs signature and nomogram to assist predict survival outcomes and clinical treatment of HCC patients. It also shows us the underlying mechanisms of different DDR patterns in HCC.